2021
DOI: 10.5861/ijrsm.2021.m7734
|View full text |Cite
|
Sign up to set email alerts
|

Service quality of online travel agencies in CALABARZON region

Abstract: In this study, the service quality of online travel agencies in CALABARZON region in terms of Tangibility, Reliability, Responsiveness, Assurance and Empathy were examined. The OTA's service performance in terms of customer satisfaction and loyalty will be analyzed in order to propose a framework of innovation for the online travel agency. The researcher used the quantitative research design to the 376 OTA employees and customers among the 120 accredited travel agencies operating in CALABARZON IV-A. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Thus, resorts should always aspire to improve their existing operational processes, specifically their service quality standards for loyal guests to keep coming back to the resort. This is supported by the study findings of Mones and Borbon et al (2021), which found that respondents with higher intentions of revisiting also had a higher willingness to pay; similarly, respondents with higher intentions of revisiting also have higher levels of loyalty. It is critical for resort operators to persuade their guests to stay in their resorts by assuring them of the provision of high-quality services.…”
Section: International Journal Of Research Studies In Management 97supporting
confidence: 73%
See 2 more Smart Citations
“…Thus, resorts should always aspire to improve their existing operational processes, specifically their service quality standards for loyal guests to keep coming back to the resort. This is supported by the study findings of Mones and Borbon et al (2021), which found that respondents with higher intentions of revisiting also had a higher willingness to pay; similarly, respondents with higher intentions of revisiting also have higher levels of loyalty. It is critical for resort operators to persuade their guests to stay in their resorts by assuring them of the provision of high-quality services.…”
Section: International Journal Of Research Studies In Management 97supporting
confidence: 73%
“…Furthermore, this suggests that resorts can motivate loyalty and willingness to pay more for this age group. This is also supported by Monterey's and Borbon's (2021) study results on service quality and performance among online travel companies in the CALABARZON area, which revealed that baby boomers have significantly lower responses to service quality. As a result, this age group's evaluation of the dimensions of behavioral intentions will also decrease.…”
Section: International Journal Of Research Studies In Management 97supporting
confidence: 65%
See 1 more Smart Citation
“…The use of online travel agency websites is still on the rise despite all of the economic issues but there may be a reduction of travel opportunities due to the pandemic. However, once the pandemic is gone, the use of online travel agencies will still be prioritized because of convenience (Monterey and Borbon, 2021). Most of the well-known online travel agencies in the Philippines are TripAdvisor, and Agoda.…”
Section: Introductionmentioning
confidence: 99%